O estágio supervisionado na construção da identidade profissional do pedagogo - CORRÊA, Joyce Docarmo (2019)
The present research was developed from the investigation of how it happened to the discipline of Supervised Internship in the Pedagogy Course of UFPA – Abaetetuba Campus. In this sense, the general objective was to understand the contribution of the supervised internship in the construction of the professional identity of the pedagogue, since this Discipline should provide students with the contact with their work environment, so that they can develop a reflexive practice from their performance and thus build their professional identity. Thus, the research is qualitative, with emphasis on the documental analysis of the Pedagogical Project of the Course (1999) in force and a focus group interview with six students of the pedagogy classes 2015 (morning and evening), aiming to apprehend with the speeches of them the meaning that the discipline had for its formation. The data analyzed showed that the supervised internship is of paramount importance in the construction of the professional identity of the students, however the way in which it was done left gaps in this training, which demands a reformulation of the current PPC (1999), indicating new possibilities for the realization of the supervised internship in the course. With this research, we then contribute to the discussions about the formation of the pedagogue, emphasizing the importance of the Supervised Internship as a formative process in the construction of the identity of this professional.